Blowin' in the Wind of an Invisible Killer: Long-Term Exposure to Ozone and Respiratory Mortality in the United States - Ziheng Liu; Xi Chen; Qinan Lu (Institute of Labor Economics (IZA), 2023)
In light of the low public awareness of ozone pollution and the potential health threats posed by long-term ozone exposure, this study estimates the causal effect of long-term ozone exposure on respiratory mortality. By employing an instrumental variable based on the long-distance transmission of ozone from upwind neighbor counties, we discover that an increase of one standard deviation in the average concentrations of ozone in the preceding five years increases respiratory mortality by 0.062–0.066 standard deviations. The findings indicate that long-term ozone exposure increases mortality from both acute and chronic respiratory diseases and has significant adverse effects on vulnerable groups. Furthermore, we discover that the respiratory mortality rate responds to long-term ozone exposure nonlinearly, and that there is a critical threshold at which the adverse effects of ozone exposure commence. Our bootstrap simulation results suggest that if ozone concentrations in the preceding five years decrease by 10 percent, 11,391 deaths from respiratory diseases could be avoided in the United States annually, with resulting health benefits valued at around 106.85–113.67 billion. Our further estimates suggest that, consistent with general respiratory diseases, long-term ozone exposure also contributes to deaths from COVID-19 during the pandemic.
Keywords: I15; J14; Q51; Q53; 330; long-term exposure; ozone; respiratory diseases; nonlinear responses; health benefits; COVID-19